The doctor as jailer: medical detention of non-psychiatric patients. Issue 1 (5th July 2019) - Kersten, Charles
Abstract: Most states empower doctors to detain psychiatric patients if they pose a danger to themselves or others due to a mental illness; however, they do not cover patients whose mental status is dangerously altered due to a non-psychiatric illness, for example, an electrolyte imbalance. Physicians generally handle these 'medically incapacitated' patients by saying they lack capacity to decide to leave against medical advice. The medical and legal literature does not address the legal basis for a doctor to effectively trap a patient in the hospital. This article analyzes the laws of California to show how and under what circumstances such a detention could be justified; in doing so, it provides guidance for a legally sound policy for holding 'medically incapacitated' patients.